Livestock Development in Hanoi City, Vietnam—Challenges and Policies - Pham-Thanh, Long; Magnusson, Ulf; Can-Xuan, Minh; Nguyen-Viet, Hung; Lundkvist, Åke; Lindahl, Johanna (Frontiers in Veterinary Science, 2020)
The rapid urban growth of Hanoi city requires a livestock production system that ensures both food security and the livelihoods of dwellers. This paper reviews the existing policies for livestock production of the Hanoi city, the changes in livestock population between 2014 and 2018, and identifies major challenges for livestock development of the city. While a remarkable increase of the livestock population in recent years is evident, the dominance of small-scale farms, the presence of animal diseases, the slow progress of transiting farms out of urban areas, as well as the lack of analysis of climate change and gender impacts are major challenges that could affect the livestock development of Hanoi.